Sociodemographic factors associated with major depressive episodes and suicidal ideation among emerging adults with diabetes in the U.S - Yadav, Sandhya; Hong, Young-Rock; Westen, Sarah; Marlow, Nicole M.; Haller, Michael J.; Walker, Ashby F. (Frontiers in Endocrinology, 2023)
Higher risk of Major Depressive Episodes (MDE) for women and sexual minority (lesbian, gay, bisexual (LGB)) emerging adults with diabetes.• LGB emerging adults have an increased risk of suicidal ideation compared to their heterosexual counterparts.• Among emerging adults, Non-Hispanic Blacks have lower odds of experiencing MDE compared to non-Hispanic Whites.• Integration of mental health professionals into diabetes care team is crucial for managing comorbid mental health conditions in emerging adults with diabetes.